Profil Pasien Katarak di Poliklinik Mata RS PKU Muhammadiyah Rogojampi - Ayu Dyah Annisha (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
Cataracts are the world’s second leading cause of blindness, trailing only uncorrected refractive errors. Based on the 2014-2016 RAAB survey, the blindness prevalence in 15 Indonesian provinces ranged from 1.4% in West Sumatra and 4.4% in East Java. A cataract is a clouding of the intraocular crystalline lens, in which this cloudiness can lead to a decreased vision function, and even it may trigger the emergence of blindness. The blindness caused by cataracts is preventable. This research aims to identify and collect data on the frequency of cataract patient profiles at the Eye Polyclinic of PKU Muhammadiyah Rogojampi Hospital in 2021. The research method utilized in this study was a retrospective descriptive study by applying a cross-sectional approach. The research data were attained from the secondary data, particularly in medical record examinations at PKU Muhammadiyah Rogojampi Hospital. This study was conducted from June to October 2021. The population of this research consisted of all cataract patients at PKU Muhammadiyah Rogojampi Hospital, in which the sample comprised 41 respondents. The data analysis using univariate analysis was denoted in the frequency distribution table. The results demonstrated that out of 41 respondents, 19 patients (46%) were about 60-69 years old, 26 patients (63%) were males, and 12 patients (29%) worked as farmers.